Accuracy and Safety of 1, 055 Transjugular Liver Biopsies in Postliver Transplant Patients. Issue 5 (21st May 2021) - Lee, Edward Wolfgang; Sue, Megan J.; Saab, Sammy; DiNorcia, Joseph; McWilliams, Justin P.; Kaldas, Fady; Ding, Peng-xu; Padia, Siddharth A.; Agopian, Vatche; Farmer, Douglas; Busuttil, Ronald W.
Abstract : INTRODUCTION: The purpose of this study was to investigate the rates of complications and diagnostic yield of transjugular liver biopsy (TJLB) in deceased donor liver transplant (DDLT) recipients. METHODS: From January 2009 to December 2019, 1, 055 TJLBs were performed in 603 adult DDLT recipients with a mean age of 54 (±12 years). Data were retrospectively reviewed to determine the diagnostic efficacy and incidence of major and minor complications in the 3-day and 1-month period after TJLB. In addition, data were stratified according to platelet count and international normalized ratio to determine the safety of TJLB in patients with varying degrees of coagulopathy. RESULTS: TJLB yielded diagnostic rate of 98.1% (1, 035/1, 055), with an overall complication rate of 8.3% (88/1, 055). Major complications accounted for 0.85% (9/1, 055), and minor complications occurred in 7.48% (79/1, 055). When patients were stratified by platelet count (0–50, 51–100, 101–200, 201–300, and >300 × 10 3 platelets/μL), no significant difference was noted in complication rates (9.5%, 8.6%, 7.6%, 8.5%, and 10.7%, respectively). When grouped by international normalized ratio (0–1, 1.1–2.0, 2.1–3.0, and >3.0), there was no statistical difference in complication rates (8.3%, 8.5%, 7.7%, and 0%, respectively). DISCUSSION: TJLB is a safe, adequate, and effective method to investigate hepatic disorders in DDLT recipients with severe coagulopathy.